Construction of the Azacyclic Core of Tabernaemontanine-Related Alkaloids via Tandem Reformatsky Aza-Claisen Rearrangement - Suh, Young-Ger; Lim, Changjin; Sim, Jaehoon; Lee, Jae Kyun; Surh, Young-Joon; Paek, Seung-Mann (AMER CHEMICAL SOC, 2017)
A divergent synthetic methodology for a tabernaemontanine-related alkaloid was developed. The synthetic route features practical improvements in the Pictet-Spengler cyclization for the tetrahydro-fi-carboline intermediate and an unprecedented tandem Reformatsky aza-Claisen rearrangement to create the core carbon skeleton and stereochemistries of tabernaemontanine-related alkaloids.
Keywords: ENANTIOSPECIFIC TOTAL-SYNTHESIS; INDOLE ALKALOIDS; BISINDOLE ALKALOIDS; TABEMAEMONTANA; VOBASINE